Relational autonomy in active ageing. Analysis of the WHO document - Madonna, Federica (Medicina e Morale, 2025)
The following work, taking inspiration from the analysis of active ageing, proposed by the 2002 WHO document of the same name, aims to reflect on the profound meaning of old age, as a life “experience” in which the importance of the sense of being in relationship with the other: intersubjectivity. Starting from the analysis of the meaning of active, it is clear that the thesis underlying the document, also taken up by the Opinion of the National Committee of Bioethics (CNB), is that of a change of ethical perspective, which fully embraces the principles of the Barcelona Declaration, demonstrating the urgency of abandoning the pernicious myth of the old as a “social burden”, to replace it with a different way of understanding the same concept of autonomy: no longer the prototype of the “Cartesian man”, but a gradual achievement over the course of life and not an “already given” ability. In this perspective, further reflection begins on the analysis of old age as a stage of life to be cherished and safeguarded.